2021
DOI: 10.3389/fnhum.2021.694919
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Acupuncture Therapy in Diseases Based on Magnetic Resonance Image Studies: A Literature Review

Abstract: The neural mechanisms of acupuncture are not well-understood. Over the past decades, an increasing number of studies have used MRI to investigate the response of the brain to acupuncture. The current review aims to provide an update on acupuncture therapy in disease. The PubMed, Embase, Web of Science, and Cochrane Library databases were searched from inception to January 31, 2021. Article selection and data extraction were conducted by two review authors. A total of 107 publications about MRI in acupuncture w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 147 publications
0
13
0
Order By: Relevance
“…Though using healthy subjects in the research can receive good compliance, it is difficult to characterize the effects of ARRMs on treating diseases. Thus, there is a growing trend in acupuncture neuroimaging studies to change subjects from healthy subjects to patients (Cai et al, 2018;Zhang et al, 2021). Research showed that positive results were reported in acupuncture studies on patients, while negative results were found on healthy subjects only (Qiu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Though using healthy subjects in the research can receive good compliance, it is difficult to characterize the effects of ARRMs on treating diseases. Thus, there is a growing trend in acupuncture neuroimaging studies to change subjects from healthy subjects to patients (Cai et al, 2018;Zhang et al, 2021). Research showed that positive results were reported in acupuncture studies on patients, while negative results were found on healthy subjects only (Qiu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging-based clinical efficacy prediction of acupuncture using machine learning has been an attractive research area in the field of AI-directed acupuncture, which brings a novel and promising approach to understanding the efficacy of acupuncture treatment at the individual level [ 54 ]. Neuroimaging machine learning can learn a function based on the patient clinical examination data and acupuncture efficacy.…”
Section: Ai In the Prediction Of Acupuncture Efficacymentioning
confidence: 99%
“…The electrical properties of acupuncture points include increased conductance, reduced impedance and resistance, increased capacitance, and elevated electrical potential compared with adjacent non-acupuncture points [11]. significant clinical results [22][23][24]. With regards to the activation of the primary motor cortex, it is suggested that a strong deqi sensation is required.…”
Section: The Effect Of Deqi Sensation On the Motor Cortexmentioning
confidence: 99%